2017
DOI: 10.1002/cam4.1089
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening in a low‐resource setting: a pilot study on an HPV‐based screen‐and‐treat approach

Abstract: Cervical cancer (CC) is the leading cause of cancer‐related death among women in sub‐Saharan Africa, primarily because of limited access to effective screening and preventive treatment. Our aim was to assess the feasibility of a human papillomavirus (HPV)‐based CC screen‐and‐treat approach in a low‐resource context. We recruited 1012 women aged 30–49 years through a CC screening campaign conducted in the District Hospital of Dschang, Cameroon. Participants performed HPV self‐sampling, which was tested for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 28 publications
(32 reference statements)
8
69
1
2
Order By: Relevance
“…35 In addition, GX HPV testing has met international performance standards for use in primary cervical cancer screening. 30 Several countries have piloted the GX HPV test including South Africa, 36 Cameroon, 37 UK, 30 Zambia, 38 Saudia Arabia, and the USA. 39,40 Sensitivity rates in detecting CIN2+ ranged from 63.2% to 98.7% and specificity ranged from 42.6% to 90.3%.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, GX HPV testing has met international performance standards for use in primary cervical cancer screening. 30 Several countries have piloted the GX HPV test including South Africa, 36 Cameroon, 37 UK, 30 Zambia, 38 Saudia Arabia, and the USA. 39,40 Sensitivity rates in detecting CIN2+ ranged from 63.2% to 98.7% and specificity ranged from 42.6% to 90.3%.…”
Section: Discussionmentioning
confidence: 99%
“…One way to facilitate scale‐up of molecular testing is to use point‐of‐care technologies. Performed using benchtop analyzers, point‐of‐care HPV tests would enable same‐day testing and treatment . One such testing platform (GeneXpert; Cepheid, Sunnyvale, CA, USA) is already widely available across Sub‐Saharan Africa owing to its use in the diagnosis of HIV and tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experience has demonstrated that the use of NaCl 0.9% is a valid medium for HPV analysis on Self-HPV. 18 The use of this medium, however, has not yet been proven effective for Dr-HPV. Therefore, the NaCl 0.9% was used for Self-HPV sample analysis, whereas the SurePath medium, as recommended by the manufacturers, was used for the analysis of Dr-HPV samples.…”
Section: Discussionmentioning
confidence: 99%